2019
DOI: 10.1021/acs.jpcb.8b10386
|View full text |Cite
|
Sign up to set email alerts
|

Possible Mechanisms of Nonenzymatic Formation of Dehydroalanine Residue Catalyzed by Dihydrogen Phosphate Ion

Abstract: Uncommon crosslinked amino acids have been identified in several aging tissues and are suspected to trigger various age-related diseases. Several uncommon residues are formed when the dehydroalanine (Dha) residue undergoes a nucleophilic attack by surrounding residues. Dha residues are considered to be formed by posttranslational modification of serine (Ser) and cysteine residues. In the present study, we investigated the Dha residue formation mechanism catalyzed by dihydrogen phosphate ion (H 2 PO 4 − ) using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 43 publications
1
15
0
Order By: Relevance
“… 24 In addition, our recent computational studies showed that the activation energies of Ser-residue dehydration and Dha-residue hydration were significantly higher than that of Ser-residue enolization. 25 These data supported that the Ser-residue stereoinversion mainly proceeds by keto-enol tautomerization. l -Ala- d / l -Glu epimerase is an enzyme that catalyzes keto-enol tautomerization with proton abstraction.…”
Section: Introductionmentioning
confidence: 55%
See 3 more Smart Citations
“… 24 In addition, our recent computational studies showed that the activation energies of Ser-residue dehydration and Dha-residue hydration were significantly higher than that of Ser-residue enolization. 25 These data supported that the Ser-residue stereoinversion mainly proceeds by keto-enol tautomerization. l -Ala- d / l -Glu epimerase is an enzyme that catalyzes keto-enol tautomerization with proton abstraction.…”
Section: Introductionmentioning
confidence: 55%
“…Previously, quantum chemical calculations showed that the activation energies of Ser-residue stereoinversion via enol intermediates are comparable to those of typical nonenzymatic reactions. 25 , 27 Although Dha residues are potential intermediates of Ser-residue stereoinversion, experimental and computational evidence so far has confirmed the hypothesis that Dha residues are intermediates of stereoinversion. 24 , 25 Therefore, in the present study, d - allo -Thr residue was assumed to be obtained via enolized Thr residues ( Scheme 3 ), as well as Ser-residue stereoinversion.…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…Recently, we performed benchmark studies on the mechanism of nonenzymatic Asp-residue cyclization, and showed that the calculations using B3LYP functional methods provided favorable results [34]. In addition, the activation energies for non-enzymatic modifications of amino acid residues were successfully calculated using the B3LYP/6-31+G(d,p) level of theory [23,24,25,26,27,28,29,30,35,36]. Thus, we used B3LYP/6-31+G(d,p) for this study.…”
Section: Methodsmentioning
confidence: 99%